HUBUNGAN PENGALAMAN MENULIS DI MAJALAH DINDING DENGAN KEMAMPUAN MENULIS KARANGAN NARASI OLEH SISWA KELAS X SMA TAMAN SISWA MEDAN TAHUN PEMBELAJARAN 2012/2013 - Adriani Perangin angin (Basastra, 2012)
This study aimed to describe the level of mastery of diction, illustrating the ability to write essays arguing and explaining relationships diction mastery of the ability to write essays siswa.Penelitian argument was held in SMA Negeri 1 Berastagi. Sample as many as 40 students, which is taken Random Sampling (Random) from 9 class X, and was elected class X-1 as an object of research.Before testing the hypothesis, first performed followed by descriptive data and test requirements analysis, test for normality and linearity test. To test the hypothesis used formula product moment correlation significance level of 5%. From the description of the data obtained diction skills class X SMA Negeri 1 Berastagi learning year 2012/2013, quite well with the average value of 75.625 and a standard deviation of 7.18 and an argument essay writing skills of students is also quite good with an average value of 71.625 and a standard deviation of 7.02. The correlation coefficient menunjukkanrhitung> rtabel or 0.663> 0.312 so it can be concluded that there is a significant relationship between mastery of diction on the ability to write an argument essay in class X SMA Negeri 1 Berastagi Learning Year 2012/2013. Linearity test results indicate that the relationship between Mastery Ability Test Diction for Writing Argumentation Writing ability is linear regression equation: Y = 22.624 + 0.648 X and Fhitung = 0.715> F table = 2.30. Thus the higher ability students mastery of diction, the higher the student's ability to write an argument essay. keyword, mastery of diction is associated with writing arguments.